4-Nonylphenol effects on rat testis and sertoli cells determined by spectrochemical techniques coupled with chemometric analysis. (March 2019) - Duan, Peng; Liu, Bisen; Morais, Camilo L.M.; Zhao, Jing; Li, Xiandong; Tu, Jian; Yang, Weiyingxue; Chen, Chunling; Long, Manman; Feng, Xiaobing; Martin, Francis L.; Xiong, Chengliang
Abstract: Herein, vibrational spectroscopy has been applied for qualitative identification of biomolecular alterations that occur in cells and tissues following chemical treatment. Towards this end, we combined attenuated total reflection Fourier-transform infrared (ATR-FTIR) and Raman spectroscopy to assess testicular toxicology after 4-nonylphenol (NP) exposure, an estrogenic endocrine disruptor affecting testicular function in rats and other species. Rats aged 21, 35 or 50 days received NP at intra-peritoneal doses of 0, 25, 50 or 100 mg/kg for 20 consecutive days. Primary Sertoli cells (SCs) were treated with NP at various concentrations (0, 2.5, 5, 10 or 20 μM) for 12 h. Post-exposure, testicular cells, interstitial tissue and SCs were interrogated respectively using spectrochemical techniques coupled with multivariate analysis. Distinct biomolecular segregation between the NP-exposed samples vs . control were observed based on infrared (IR) spectral regions of 3200–2800 cm −1 and 1800-900 cm −1, and the Raman spectral region of 1800–900 cm −1 . For in vivo experiments, the main wavenumbers responsible for segregation varied significantly among the three age classes. The main IR and Raman band differences between NP-exposed and control groups were observed for Amide (proteins), lipids and DNA/RNA. An interesting finding was that the peptide aggregation level, Amide Ӏ-to-Amide II ratio, and phosphate-to-carbohydrate ratio were considerably reduced in ex vivo NP-exposed testicular cells or SCs in vitro . This study demonstrates that ATR-FTIR and Raman spectroscopy techniques can be applied towards analysing NP-induced testicular biomolecular alterations. Graphical abstract: Image 1 Highlights: The extent of testicular alterations were assessed by ATR-FTIR and Raman spectroscopy. 4-Nonylphenol (NP) exposure-induced testicular toxicity is associated with biomolecular alterations. Biomolecular alterations by the age at which NP exposure started were monitored.